Organizing Catering Systems in General Educational Organizations: Foreign Experiences and Implications for Russia - Mindzaeva, Eteri; Neustroev, Sergey; Ivanova, Margarita; Zimnyukova, Nataliya (Journal of History Culture and Art Research, 2019)
The article discusses the current experiences and prospects of organizing hot meals in educational institutions in the context of health-saving technologies. The authors state that there is a tendency to develop universal requirements for a system of school feeding in each general educational organization, taking into account local conditions. Following this trend involves selecting and disseminating the best practices in organizing school nutrition in the general context of health-saving technologies. The concretization of this approach consists in analyzing the existing domestic and foreign experience in organizing school nutrition and creating an effective model of organizing a catering system. Such an effective model is understood as a set of organizational elements that comprehensively ensure the process of organizing a catering system in a general education organization that meets requirements of the regulatory framework existing in the Russian Federation, as well as taking into account certain territorial, climatic, geographical, ethnic, cultural, socio-economic, and other features of a particular region. More than that, the authors argue that such a model should address the population’s level and way of life, as well as students’ number, age, and individual needs.